Phytohormone and integrated mRNA and miRNA transcriptome analyses and differentiation of male between hermaphroditic floral buds of andromonoecious Diospyros kaki Thunb - Li, Huawei (BMC Genomics, 2021)
BACKGROUND: Persimmon (Diospyros kaki Thunb.) has various labile sex types, and studying its sex differentiation can improve breeding efficiency. However, studies on sexual regulation patterns in persimmon have focused mainly on monoecy and dioecy, whereas little research has been published on andromonoecy. In order to reveal the sex differentiation regulation mechanism of andromonoecious persimmon, we performed histological and cytological observations, evaluated OGI and MeGI expression and conducted phytohormones assays and mRNA and small RNA transcriptome analyses of the male and hermaphroditic floral buds of the andromonoecious persimmon ‘Longyanyeshi 1’. RESULTS: Stages 2 and 4 were identified as the critical morphological periods for sex differentiation of ‘Longyanyeshi 1’ by histological and cytological observation. At both stages, OGI was differentially expressed in male and hermaphroditic buds, but MeGI was not. This was different from their expressions in dioecious and monoecious persimmons. Meantime, the results of phytohormones assays showed that high IAA, ABA, GA(3), and JA levels at stage 2 may have promoted male floral bud differentiation. However, high JA levels at stage 4 and high ZT levels at stages 2 and 4 may have promoted hermaphroditic floral bud differentiation. In these phytohormone biosynthesis and signaling pathways, 52 and 54 differential expression genes (including Aux/IAA, ARFs, DELLA, AHP, A-ARR, B-ARR, CYP735A, CRE1, PP2C, JAZ, MYC2, COI1, CTR1, SIMKK, ACO, and MPK6) were identified, respectively. During the development of male floral buds, five metacaspases genes may have been involved in pistil abortion. In addition, MYB, FAR1, bHLH, WRKY, and MADS transcription factors might play important roles in persimmon floral bud sex differentiation. Noteworthy, miR169v_1, miR169e_3, miR319_1, and miR319 were predicted to contribute to phytohormone biosynthesis and signaling pathways and floral organogenesis and may also regulate floral bud sex differentiation. CONCLUSION: The present study revealed the differences in morphology and phytohormones content between male and hermaphroditic floral buds of ‘Longyanyeshi 1’ during the process of sex differentiation, and identified a subset of candidate genes and miRNAs putatively associated with its sex differentiation. These findings can provide a foundation for molecular regulatory mechanism researching on andromonoecious persimmon. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12864-021-07514-4.